(untitled) (Bangladesh Agronomy Journal, 2024)
An experiment was carried out at the Regional Sugarcrop Research Station (RSRS) farm, Thakurgaon under the agro-ecological zone of Old Himalayan Piedmont Plain (AEZ-1) of Bangladesh, during 2016-2017 to 2017-2018 cropping seasons to evaluate the impact of row orientation on the productivity of sugarcane with potato as intercrop. Under the study eight treatments viz T1: Single row cane (SRC) only in north-south direction, T2: SRC + potato in North-South direction, T3: SRC only in east-west direction, T4: SRC + potato in east-west direction,T5: Paired row cane (PRC) only in North-South direction, T6: PRC + potato in north-south direction, T7: PRC only in east-west direction and T8: PRC + potato in east-west direction were tested following Randomized Complete Block Design with three replications Significant differences were found among the observed parameters except germination (%) of setts, number of internodes per stalk and unit stalk weight of sugarcane. The highest number of tiller and millable cane population, cane yield and brix reading were achieved from the treatment SRC + potato in the North-South direction. The highest intercrop yield, equivalent cane yield of intercrop, total adjusted yield and gross return were obtained from the treatment PRC + potato in north-south direction, but the highest net return and benefit cost ratio were obtained from the treatment SRC + potato in the North-South direction. Having the highest cane yield, net return and benefit cost ratio with less variable cost, sugarcane planting in a single row system with potato as intercrop in a North-South row direction could be considered the best package practice for successful sugarcane farming. Bangladesh Agron. J. 2024, 26(2): 7-15